Considerations for Financial Facilities to Support Water Utilities in the COVID-19 Crisis - World Bank (World Bank, Washington, DC, 2020)
The objective of this document is to lay out the options and considerations in the design of facilities to provide emergency financial support to water utilities in response to the COVID-19 pandemic. It builds on the experiences of previous financial crises (such as the global financial crisis of 2007–08 and the Asian Financial Crisis of 1997), including their impact and responses to them. Its main audience is government policy makers trying to develop financial responses to ensure utilities continue to function during the crisis, as well as the World Bank country teams and Task Team Leaders assisting them. The type of facility described in this document may be based on an existing one or related mechanisms (fiscal transfers, guarantees, subsidy programs, or others), or it could be the kernel of a new institution or financing instrument that may continue to have a role in sector financing after the crisis. Considering this, the paper recognizes that there will likely be a need to consider new external borrowing in the context of ensuring macroeconomic and fiscal stability. Many emerging markets were already showing signs of over-indebtedness before the COVID-19 crisis and the costs associated with the pandemic will only increase the demand for resources, including public debt. Macro-economic stability must be anchored on sustainable paths of public and external debt, and countries will need to consider this in coordination with ongoing initiatives by the Group of Twenty (G20), the International Monetary Fund (IMF), and others to ensure debt sustainability and transparency.